Auxin Transport: A New Synthetic Inhibitor - Beyer, Elmo M. (1972)
The new synthetic plant growth regulator DPX1840 (3,3a-dihydro-2-(p-methoxyphenyl)-8H-pyrazolo [5,1-a] isoindol-8-one) was examined for its effects on auxin transport. At a concentration of 0.5 mm in the receiver agar cylinders DPX1840 significantly inhibited the basipetal transport of naphthaleneacetic acid-1-(14)C in stem sections of Vigna sinensis Endl., Pisum sativum L., Phaseolus vulgaris L., Glycine max L., Helianthus annuus L., Gossypium hirsutum L., and Zea mays L. without significantly reducing total auxin uptake or recovery. The time sequence of the effect varied with the plant species. A similar inhibition of the basipetal movement of indoleacetic acid-1-(14)C was observed in intact seedlings of Phaseolus vulgaris L. In contrast to basipetal auxin transport DPX1840 had no significant effect on the acropetal movement of indoleacetic acid-1-(14)C in stem sections of Gossypium hirsutum L. Qualitatively the effect of DPX1840 on basipetal auxin transport was similar to that of other known auxin transport inhibitors. Quantitative differences, however, suggested the following order of activity: Naptalam>morphactin[unk]DPX1840>2,3,5-triiodobenzoic acid. DPX1840 also inhibited the lateral displacement of auxin. In horizontally placed stem sections of Helianthus annuus L. pretreated with DPX1840, the ratio of radioactivity from indoleacetic acid-1-(14)C in the upper versus the lower halves of the sections following basipetal indoleacetic acid-1-(14)C transport was approximately 50:50, whereas in the corresponding controls it was approximately 40:60. The data indicate that many of the characteristic effects of DPX1840 on plants, especially those which are known to involve auxin (e.g., epinasty, abscission, apical dominance, tropism), are due, at least in part, to its effects on auxin transport.